Wideband mimo antenna development for wireless communication - Abdul Wafiy, Kassim (2021)
This paper is focusing on filter designs capable of operating in 2.4GHz and 3.5GHz to 4.2GHz, the new radio frequency sub 6GHz. In this decade, it saturated with wireless technology resulting in increasing of wireless power density as there is an increasing number of electromagnetic (EM) sources such as cellular mobile base stations, digital TV towers and Wi-Fi transmitters. In recent years, the idea of using radio frequency (RF) power for low power electronic devices has been gaining momentum to replace batteries and save on maintenance costs. To begin with, an integrated device that include MIMO antenna, filter and energy harvesting circuit has been fabricated. In this dissertation, a microstrip dual-band bandpass is proposed and designed to operate at 2.4GHz and 3.5GHz to 4.2GHz without requiring any external impedance matching block. With two dual arms patch design and defected ground structure (DGS), the filter was designed using High Frequency Structure Simulator (HFSS). The simulation resulted in less return loss at the targeted frequency.